Towards infinity: the imperfect integral through the eyes of a student - Bo’ronova Dinora Kholmat Qizi (Jurnal Pendidikan Indonesia : Teori, Penelitian, dan Inovasi, 2026)
This article explores the concept of the imperfect integral from a student’s perspective, highlighting the challenges and misconceptions that arise during the learning process. By analyzing common pitfalls and providing insights into effective strategies for grasping this mathematical concept, the article aims to bridge the gap between theoretical understanding and practical application. Through a combination of illustrative examples and personal experiences, it offers readers a unique viewpoint on how students can better navigate the complexities of the imperfect integral and foster a deeper appreciation for calculus.ANNOTATSIYAUshbu maqola mukammal bo'lmagan integral tushunchasini talaba nuqtai nazaridan o'rganib, o'rganish jarayonida yuzaga keladigan qiyinchiliklar va noto'g'ri tushunchalarni yoritadi. Keng tarqalgan xatolarni tahlil qilish va bu matematik tushunchani anglash uchun samarali strategiyalar bo'yicha tavsiyalar berish orqali maqola nazariy tushuncha bilan amaliy qo'llash o'rtasidagi bo'shliqni to'ldirishni maqsad qiladi. Illyustrativ misollar va shaxsiy tajribalarni birlashtirgan holda, u o'quvchilarga kamchilikli integralning murakkabliklarini yaxshiroq yengib o'tish va kalkulyusga chuqurroq qadr-qimmat berish bo'yicha noyob nuqtai nazarni taklif etadi.